Model pembelajaran contextual teaching and learning untuk meningkatkan hasil belajar matematika - I Komang Karyasa (Indonesian Journal of Educational Development, 2021)
This classroom action research was carried out at SMA Negeri 6 Denpasar Class XII IPA3 in the odd semester of the 2018/2019 academic year on the subject of mathematics in Three Dimensions (Building Space) material, aims to improve learning achievement in Mathematics through the application of Contextual Teaching and Learning (CTL) models. The data from this research were collected by giving learning achievement tests. In analyzing the data obtained used descriptive analysis method. The data generated from this study consisted of initial data, data from cycle I and data from cycle II. From the preliminary data, it was obtained that the average new class reached a value of 71.89 and the learning completeness only reached 47.37%. This data is far below expectations considering the KKM for Mathematics in this school is 75.00. In the first cycle there has been an increase, namely the class average reached 74.39 and the percentage of completeness in learning reached 71.05%. In the second cycle the grade average acquisition has reached 86.87 and the percentage of completeness in learning has reached 97.37%. The data in Cycle II are as expected due to the use of a contextual learning model. The conclusions that can be conveyed by applying the contextual teaching and learning model can improve student learning achievement. Penelitian tindakan kelas ini dilaksanakan di SMA Negeri 6 Denpasar Kelas XII IPA3 semester ganjil tahun pelajaran 2018/2019 pada mata pelajaran matematika pokok bahasan Dimensi Tiga (Bangun Ruang), bertujuan untuk meningkatkan prestasi belajar pada mata pelajaran Matematika melalui penerapan model pembelajaran Contextual Teaching and Learning (CTL). Data hasil penelitian ini dikumpulkan dengan cara pemberian tes prestasi belajar. Dalam menganalisis data yang diperoleh digunakan metode analisis deskriptif. Data yang dihasilkan dari penelitian ini terdiri dari data awal, data siklus I dan data Siklus II. Dari data awal diperoleh rata-rata kelas baru mencapai nilai 71,89 dan ketuntasan belajarnya baru mencapai 47,37%. Data ini jauh di bawah harapan mengingat KKM mata pelajaran Matematika di sekolah ini adalah 75,00. Pada siklus I sudah terjadi peningkatan yaitu rata-rata kelasnya mencapai 74,39 dan persentase ketuntasan belajar mencapai 71,05%. Pada siklus II perolehan rata-rata kelas sudah mencapai 86,87 dan persentase ketuntasan belajarnya sudah mencapai 97,37%. Data pada Siklus II ini sudah sesuai harapan akibat penggunaan model pembelajaran yang sifatnya kontekstual. Kesimpulan yang dapat disampaikan dengan penerapan model pembelajaran contextual teaching and learning dapat meningkatkan prestasi belajar siswa.